Common Structural Lesions of the Peripheral Nervous System. (January 2020) - Jortner, Bernard S.
This review illustrates common lesions of peripheral nerve myelinated fibers that occur in toxic neuropathy. These distinctive structural changes help to define the site of toxicant activity and thus predict the course of neurotoxic disease and recovery. Neuronopathy is the condition where the primary injury is directed to the neuronal cell body giving rise to a peripheral nerve axon. Axonopathy occurs when the axon is the primary target, and myelinopathy develops where the Schwann cell and/or myelin sheath is the primary target; these conditions can be discriminated early during the course of nerve fiber degeneration, but reciprocal influences between axon and myelin result in degeneration of both structures late in the disease.